Obesity and lumbar fusion: increased risk of blood loss. (3rd June 2015) - Jewett, GA; Yavin, D; Sahota, IS; Dhaliwal, P; Du Plessis, S
Abstract : Background: Several studies have demonstrated that obese patients are at increased risk of perioperative complication during lumbar spine surgery. Herein we quantify the association between blood loss and obesity during lumbar fusion. Methods: Outcomes were collected in the setting of a single center randomized control trial conducted among patients undergoing elective lumbar fusion. A univariate analysis of potential risk factors (gender, age, body mass index [BMI], number of levels fused, previous use of anticoagulants, and previous use of non-steroidal anti-inflammatories) for operative blood loss was performed. Logistic regression was conducted to estimate adjusted odds ratios (ORs) and 95% confidence intervals. Results: Among 85 patients, the mean estimated blood loss (EBL) was 563 ml, 47.1% were male, and the median number of levels fused was one. Obesity (BMI ≥30−kg/m2) was a significant risk (OR 2.46, P=0.025) for increased blood loss (EBL > 500 ml). Number of levels fused was similarly associated with EBL (P<0.01) while gender confounded the association between obesity and EBL. Conclusions: Surgeons should anticipate greater blood loss when performing lumbar fusion in obese patients. To reduce operative morbidity, consideration should be given to preoperative weight loss whenever possible.